Apigenin-Mn(II) loaded hyaluronic acid nanoparticles for ulcerative colitis therapy in mice - Lv, Feng; Zhang, Yuchen; Peng, Qiao; Zhao, Xinxin; Hu, Datao; Wen, Jinpeng; Liu, Kailai; Li, Ruilin; Wang, Ke; Sun, Jinyao (Frontiers in Chemistry, 2022)
Ulcerative colitis (UC) is a chronic idiopathic inflammatory bowel disease characterized by rapid progression and frequent comorbidities that make its treatment challenging. Nanomaterial-based strategies have been extensively studied to target the GI mucosal immune system in recent years. Herein, we propose a novel apigenin-Mn(II) loaded sodium hyaluronate nanoparticles where apigenin (API) was incorporated in the Mn2+ ramework, coated with hyaluronic acid. The apigenin-Mn(II) loaded sodium hyaluronate nanoparticles (API-Mn(II)@HA NPs) exhibited a diameter of 200 nm and were effective against UC. The preparation of the API-Mn(II) complex was relatively simple, and the mechanism underlying its therapeutic effect on UC induced by sodium dextran sulfate (DSS) was studied in detail. We found that API-Mn(II)@HA nanoparticles could effectively repair the intestinal barrier and significantly improve the damaged colon tissue by mediating inflammatory factors. This study provides novel insights on a new kind of active targeted nanoparticle for improving the efficacy of drugs for UC treatment.